Ups and downs of public attention on climate change: the southern Brazil floods through Anthony Downs’s issue-attention cycle - Lefèvre, Guilherme Borba; Assis, Ana Paula Aprígio; Caldas , Eduardo de Lima (Sustainability in Debate, 2025)
This article analyses the public attention in Brazil to the 2024 extreme weather event in Rio Grande do Sul, focusing on the problem of climate change. The study aimed to assess whether public opinion followed Downs’ (1972) “Issue-Attention Cycle” or displayed a different pattern. Using a content analysis of the term “climate change” on the Folha de São Paulo website, over 3 months before and 6 months after the event, we found a sharp increase in climate change-related coverage following the f loods, indicating increased public interest. However, this surge in attention was short-lived, with a significant decline in approximately 30 days after the event. These results suggest that public attention to climate change issues is intense but fleeting, posing challenges for policymakers and other actors seeking to leverage this “window of opportunity” to advance climate-related public policies.